Sztuki pasyjne po irlandzku, czyli kobiety i śmierć u Oskara Wilde’a i Mariny Carr - O’Keefe, Katherine (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
A little more than century apart from each other, Oscar Wilde and Marina Carr each took clear inspiration from antiquity to write intensely symbolic drama for their times, featuring powerful female characters with fatal impulses. The article intends to examine resonances between Oscar Wilde’s Salome and The Duchess of Padua and the more recent dramas by Marina Carr. In their complex interactions of desire, guilt, evocations of blood sacrifice, and an impulse towards death, these plays may offer a possibility of transcendence.